2015
DOI: 10.1109/tcsi.2015.2476319
|View full text |Cite
|
Sign up to set email alerts
|

New Approach to the Reduction of Sign-Extension Overhead for Efficient Implementation of Multiple Constant Multiplications

Abstract: Sign-extension of operands in the shift-add network of multiple constant multiplication (MCM) results in a significant overhead in terms of hardware complexity as well as computation time. This paper presents an efficient approach to minimize that overhead. In the proposed method, the shift-add network of an MCM block is partitioned into three types of sub-networks based on the types of fundamentals and interconnections they involve. For each type of sub-network, a scheme which takes the best advantage of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This leads to an important overhead in speed, power, and area. To reduce the sign extension (SE) overhead in MCM, many approaches have been proposed, notably the MCM block partitioning [27] and positive offset [28] methods which exhibit the best results in speed and area, respectively. The conventional SE approach (CSEA) used traditionally in variable multiplication ( Y × X ) offers rather a good compromise in MCM [27], especially when both area and power are a concern.…”
Section: Bit‐level Version Of Radix‐2rmentioning
confidence: 99%
See 2 more Smart Citations
“…This leads to an important overhead in speed, power, and area. To reduce the sign extension (SE) overhead in MCM, many approaches have been proposed, notably the MCM block partitioning [27] and positive offset [28] methods which exhibit the best results in speed and area, respectively. The conventional SE approach (CSEA) used traditionally in variable multiplication ( Y × X ) offers rather a good compromise in MCM [27], especially when both area and power are a concern.…”
Section: Bit‐level Version Of Radix‐2rmentioning
confidence: 99%
“…To reduce the sign extension (SE) overhead in MCM, many approaches have been proposed, notably the MCM block partitioning [27] and positive offset [28] methods which exhibit the best results in speed and area, respectively. The conventional SE approach (CSEA) used traditionally in variable multiplication ( Y × X ) offers rather a good compromise in MCM [27], especially when both area and power are a concern. Comparatively with [27, 28], CSEA is very easy to be used: the SE is performed locally between successive PPs, assuring that at each stage, the partial sum contains the sum of the sign bits of previous PPs.…”
Section: Bit‐level Version Of Radix‐2rmentioning
confidence: 99%
See 1 more Smart Citation
“…In LS, as the critical path delay (CPD) increases, the energy per operation increases and the operating frequency decreases [10]. In [11,12], the authors found constant bit widths [20], whereas the GE require more computational resources due to a larger search space [22].…”
Section: Introductionmentioning
confidence: 99%